2021
DOI: 10.1001/jamacardio.2021.0660
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dapagliflozin on Cardiovascular Outcomes According to Baseline Kidney Function and Albuminuria Status in Patients With Type 2 Diabetes

Abstract: IMPORTANCE Sodium-glucose cotransporter 2 inhibitors, such as dapagliflozin, promote renal glucose excretion and reduce cardiovascular (CV) deaths and hospitalizations for heart failure (HHF) among patients with type 2 diabetes. The relative CV efficacy and safety of dapagliflozin according to baseline kidney function and albuminuria status are unknown. OBJECTIVE To assess the CV efficacy and safety of dapagliflozin according to baseline estimated glomerular filtration rate (eGFR) and urinary albumin to creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 33 publications
1
14
0
1
Order By: Relevance
“…The secondary analysis of the Dapagliflozin Effect on Cardiovascular Events-Thrombolysis in Myocardial Infarction (DECLARE-TIMI) 58 randomized clinical trial found no heterogeneity in the effect on HHF across DKD markers (eGFR <60 mL/min/1.73 m 2 and albuminuria) and reported a larger effect in patients with albuminuria plus decreased eGFR. 33 The current study demonstrated that participants with decreased eGFR only had a higher risk of HHF than participants without DKD, and the finding remained unchanged after excluding participants with baseline eGFR <30 mL/min/1.73 m 2 . As the study combined patients with either reduced eGFR or albuminuria as one group, 33 it remains to be confirmed how much patients with reduced eGFR in the absence of albuminuria would benefit from this drug.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 46%
See 1 more Smart Citation
“…The secondary analysis of the Dapagliflozin Effect on Cardiovascular Events-Thrombolysis in Myocardial Infarction (DECLARE-TIMI) 58 randomized clinical trial found no heterogeneity in the effect on HHF across DKD markers (eGFR <60 mL/min/1.73 m 2 and albuminuria) and reported a larger effect in patients with albuminuria plus decreased eGFR. 33 The current study demonstrated that participants with decreased eGFR only had a higher risk of HHF than participants without DKD, and the finding remained unchanged after excluding participants with baseline eGFR <30 mL/min/1.73 m 2 . As the study combined patients with either reduced eGFR or albuminuria as one group, 33 it remains to be confirmed how much patients with reduced eGFR in the absence of albuminuria would benefit from this drug.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 46%
“…33 The current study demonstrated that participants with decreased eGFR only had a higher risk of HHF than participants without DKD, and the finding remained unchanged after excluding participants with baseline eGFR <30 mL/min/1.73 m 2 . As the study combined patients with either reduced eGFR or albuminuria as one group, 33 it remains to be confirmed how much patients with reduced eGFR in the absence of albuminuria would benefit from this drug.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 46%
“…In this regard, the DECLARE study in T2DM patients with or at risk of atherosclerotic cardiovascular disease found that treatment with dapagliflozin was associated with a 24% reduction in the renal endpoint (hazard ratio, 0.76; 95% CI, 0.67–0.87). These findings demonstrate the effect of an SGLT2i in earlier stages of renal disease since in this study, 65% of patients showed no expression of any renal markers (eGFR < 60 mL/min/1.73 m 2 , microalbuminuria or macroalbuminuria: 93% showed eGFR > 60 mL/min/1.73 m 2 and 69.1% showed no albuminuria) and 59.4% of patients had no previous cardiovascular disease [ 24 , 25 ]. Interestingly, the use of SGLT2i seems to prevent and reduce diabetic kidney disease progression compared to placebo in this large and diverse population study in T2DM patients with or without established atherosclerotic cardiovascular disease, most of whom had preserved renal function.…”
Section: Discussionmentioning
confidence: 61%
“…Auch in den Langzeitstudien zu mikrovaskulären Endpunkten mit der Substanzklasse der SGLT-2 Inhibitoren (SGLT-2 = sodium glucose transporter) wurde die anhaltende prozentuale Abnahme der GFR als ein Endpunkt betrachtet [58,59,60,61,62,63,64,65,66,67,68,69,70,71]. Eine Verdopplung des Serum-Kreatinins ist ein besonders starker Prädiktor für eine Nierenerkrankung im Endstadium.…”
Section: Diabetic Retinopathy Severity Scale (Drss)unclassified